PENGEMBANGAN MODEL PEMBELAJARAN DESAIN GRAFIS BERBASIS NETOP SCHOOL DI SMK NEGERI 2 KOTA BIMA - Fitrianingsih, Nur (JURNAL ILMIAH MATRIK, 2016)
Abstract: This research is a development that aims to develop a learning model based graphic design NETOP School on Multimedia Skills Competency SMK NEGERI 2 KOTA BIMA. Subject trials are the students of class XII Multimedia numbered 31 people. ADDIE development model is a model consists of five stages: analysis, design, development, implementation and evaluation. Learning developed has been validated by experts and have revisions, and has been tested (individuals, small groups, and limited) to obtain a decent result. The results showed that the learning-based graphic design NETOP School has met the criteria of validity and is said to be effectively viewed from the activities of teachers on learning and student activity in the learning process is a very active and positive student response to learning that has been developed. Keywords: Development,Graphic Design, NETOP School